VILLAGE GOVERNMENT LEADERSHIP STYLE IN COMMUNITY ECONOMIC EMPOWERMENT (Case Study of Village-Owned Enterprise (BUMDes) Development in Pacellekang Village, Pattallasang Subdistrict, Gowa Regency) - Nasiratunnisaa Mallappiang; Abdul Muis Mappalotteng (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to evaluate the leadership style at the village level in advancing the community’s economy, with a focus on the development of the Village-Owned Enterprise (BUMDes) in Pacellekang Village, Pattallasang Subdistrict, Gowa Regency. This research employs a qualitative method, with data collected through in-depth interviews, observations, and document analysis. The participants in this study include the village head, village officials, BUMDes managers, members of the Village Consultative Body (BPD), community leaders, and local residents. The findings indicate that the most commonly applied leadership styles are democratic, participatory, and transformational leadership. Democratic leadership encourages community involvement in decision-making processes through village deliberation forums, while participatory leadership ensures community engagement at every stage of development—from planning to evaluation. Meanwhile, transformational leadership motivates the community to innovate, develop individual skills, and maximize local potential. The implementation of these leadership models contributes to enhancing the capacity of village human resources through various training and mentoring programs, strengthening socio-economic independence, and creating more equitable community welfare. Several factors support the success of empowerment initiatives, including strong support from village authorities, active community participation, and transparent BUMDes management. However, challenges remain, such as limited human resources, low technological adoption, and difficulties in ensuring equitable distribution of program benefits. This study recommends that the village government strengthen democratic and transformational leadership, enhance the capacity of village human resources, and optimize the role of BUMDes as a sustainable tool for community economic empowerment...